EXAMPLES OF IHTISAR AND NAHIV AS A FACT OF THE ARABIC LANGUAGE - TURGUT, Abdulhamit (Atlas Journal, 2022)
Ihtisar is a concept that expresses many meanings in one word in the Arabic language. The conciseness inherent in the Arabic language has attracted the attention of linguists since the first period of syntax and all linguists have commented on this issue. Like all linguistic phenomena, many factors played a role in the emergence of the concept of abbreviation. Some of these factors are specific to the Arabic language. Some of these are reasons that linguists refer to when creating syntax rules. The main reasons for abbreviation are the nature of the Arabic language, the beautification of the word, the convenience of the speaker and the listener, its interpretation and the purpose of relying on the understanding capacity of the addressee. The unconditional emergence of this fascinating subject of the Arabic language is unthinkable. It is necessary to make abbreviation in the language; We will try to address situations such as the fact that the abbreviation does not harm the soundness and understanding of the meaning, that the abbreviation is in accordance with the rules of the Arabic language, that the abbreviation is not shortened a second time. In addition, for a better understanding of the subject, we will consider examples of nekra, ma'rife nidâ, istifham, condition, ism-i verb, number and implication in the context of syntax.